Concepts and Analyses in the CT Scanning of Root Systems and Leaf Canopies: A Timely Summary - Lafond, Jonathan A.; Han, Liwen; Dutilleul, Pierre (Frontiers in Plant Science, 2015)
Non-medical applications of computed tomography (CT) scanning have flourished in recent years, including in Plant Science. This Perspective article on CT scanning of root systems and leaf canopies is intended to be of interest to three categories of readers: those who have not yet tried plant CT scanning, and should find inspiration for new research objectives; readers who are on the learning curve with applications – here is helpful advice for them; and researchers with greater experience – the field is evolving quickly and it is easy to miss aspects. Our conclusion is that CT scanning of roots and canopies is highly demanding in terms of technology, multidisciplinarity and big-data analysis, to name a few areas of expertise, but eventually, the reward for researchers is directly proportional!